Propofol increases the Ca2+ sensitivity of BKCa in the cerebral arterial smooth muscle cells of mice - Liu Xue-ru; Tan Xiao-qiu; Yang Yan; Zeng Xiao-rong; Tang Xian-ling (Acta Pharmacologica Sinica, 2016)
Aim: Propofol has the side effect of hypotension especially in the elderly and patients with hypertension. Previous studies suggest propofol-caused hypotension results from activation of large conductance Ca2+-sensitive K channels (BKCa). In this study, the effects of propofol on the Ca2+ sensitivity of BKCa were investigated in mice cerebral arterial smooth muscle cells. Methods: Single smooth muscle cells were prepared from the cerebral arteries of mice. Perforated whole-cell recoding was conducted to investigate the whole-cell BKCa current and spontaneous transient outward K+ current (STOC). Inside-out patch configuration was used to record the single channel current and to study the Ca2+- and voltage-dependence of BKCa. Results: Propofol (56 and 112 μmol/L) increased the macroscopic BKCa and STOC currents in a concentration-dependent manner. It markedly increased the total open probability (NPo) of single BKCa channel with an EC50 value of 76 μmol/L. Furthermore, propofol significantly decreased the equilibrium dissociation constant (Kd) of Ca2+ for BKCa channel. The Kd value of Ca2+ was 0.881 μmol/L in control, and decreased to 0.694, 0.599 and 0.177 μmol/L, respectively, in the presence of propofol 28, 56 and 112 μmol/L. An analysis of the channel kinetics revealed that propofol (112 μmol/L) significantly increased the open dwell time and decreased the closed dwell time, which stabilized BKCa channel in the open state. Conclusion: Propofol increases the Ca2+ sensitivity of BKCa channels, thus lowering the Ca2+ threshold of the channel activation in arterial smooth muscle cells, which causes greater vasodilating effects.